The human histaminergic system in neuropsychiatric disorders. Issue 3 (March 2015) - Shan, Ling; Bao, Ai-Min; Swaab, Dick F.
Highlights Neuronal histamine production shows a diurnal rhythm, but not in neurodegeneration. The histaminergic system shows alterations in various neuropsychiatric disorders. Animal models for these disorders only partly mimic these histaminergic alterations. Thus, postmortem human brain material is crucial to study these disorders.